Immune cells mediate the causal relationship between uveitis and colorectal cancer via Mendelian randomization analysis - Li Zhou; Jiwang Zhang (Scientific Reports, 2024)
Abstract Colorectal cancer (CRC) is one of the most common and deadly malignancies worldwide, and immune regulation plays a critical role in its development. This study investigates the causal relationships between uveitis, specific immune cell traits, and CRC using Mendelian Randomization (MR) analyses. A total of 21 single nucleotide polymorphisms (SNPs) associated with uveitis were identified, and the analysis revealed that a 1 log-odds increase in uveitis was linked to a statistically significant 3.0% reduction in CRC odds (IVW OR = 0.970, 95% CI: 0.946–0.995, P = 0.021). This protective effect was also observed using the weighted median approach (OR = 0.963, 95% CI: 0.931–0.997, P = 0.034), reinforcing the robustness of the findings. Furthermore, both univariable and multivariable MR analyses highlighted the significant causal influence of specific immune cell traits on CRC odds. Notably, the levels of extracellular monocyte HLA-DR expression emerged as a critical factor, with an associated increase in CRC odds (IVW OR = 1.084, 95% CI: 1.008–1.165, P = 0.030). The proportion of CRC odds mediated by the levels of extracellular monocyte HLA-DR expression, calculated as the ratio of the indirect effect to the total effect using estimates from multivariable MR analyses, was approximately 34.1%(95% CI: 10.23−58.04%). These findings underscore the complex interplay between immune regulation and carcinogenesis, offering insights into potential mechanisms underlying CRC development and suggesting avenues for targeted prevention and therapeutic strategies.